A comparison of the chemical, microbiological and sensory characteristics of bovine and ovine halloumi cheese - Robinson, Richard; Papademas, Photis (My University, 2000)
Commercial samples of fresh and mature Halloumi cheeses made from ovine or bovine milk were studied in order to establish their chemical, microbiological and sensory characteristics. Significant differences were observed between the two types of Halloumi cheese both when fresh and mature. The free volatile fatty acid (FVFA) content of the cheeses increased with maturation from 483 to 1356 mg kg-1 for the ovine product, but lower values (380-1248 mg kg-1) were found in the bovine cheese. During maturation for 40 days, Enterococcus faecium, which dominated the microflora of fresh ovine cheese, was replaced by lactobacilli, including a new species, Lactobacillus cypricasei, which was not found in the bovine samples. Fewer than 100 cfu g-1 lactic acid bacteria (LAB) were present in the fresh bovine cheeses, but a microflora dominated by lactobacilli developed with time. Yeast counts in the mature ovine and bovine cheeses reached 2.3-2.8 × 105 cfu g-1 and, as some of the yeasts were proteolytic and/or lipolytic, it was assumed that they were having a positive impact of the flavour of the cheeses. The sensory panel distinguished significant differences in texture and flavour between the fresh and mature samples of both ovine and bovine cheeses and, overall, there was a significant preference for the ovine brand
Keywords: Cheese; Microbiology; Milk; Sheep